2017
DOI: 10.1186/s13104-017-2762-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise type on smoking cessation: a meta-analysis of randomized controlled trials

Abstract: BackgroundExercise is one choice of additional treatment for smoking cessation by relieving nicotine withdrawal symptoms and smoking craving. The possible mechanism of the effect of exercise on relieving nicotine withdrawal symptoms and smoking craving is including affect, biological, and cognitive hypotheses. Evidence suggests that different types of exercise have different effects on these mechanisms. Therefore, type of exercise might have effect on smoking cessation. The purpose of this study is to systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 77 publications
(137 reference statements)
4
36
0
Order By: Relevance
“…All other outcomes were addressed by between one and three studies; for all outcomes reported by two or more studies, results were mixed, except in the case of depression, for which no study reported improvements. Overall, these findings reflect reviews and meta-analyses of all forms of exercise in nicotine dependence (23, 25, 100), namely that current study quality prohibits clear statements about effectiveness. Specifically, “Further studies are required to establish the optimum intensity of exercise intervention required […]” (23).…”
Section: Summary Of Main Findings Regarding Primary Outcomessupporting
confidence: 52%
See 1 more Smart Citation
“…All other outcomes were addressed by between one and three studies; for all outcomes reported by two or more studies, results were mixed, except in the case of depression, for which no study reported improvements. Overall, these findings reflect reviews and meta-analyses of all forms of exercise in nicotine dependence (23, 25, 100), namely that current study quality prohibits clear statements about effectiveness. Specifically, “Further studies are required to establish the optimum intensity of exercise intervention required […]” (23).…”
Section: Summary Of Main Findings Regarding Primary Outcomessupporting
confidence: 52%
“…The majority of these have focussed on nicotine dependence, with some positive effects found for craving (22), duration of abstinence (23), and withdrawal symptoms (24). However, results of a meta-analysis of randomized controlled trials found no effects for most forms of exercise on smoking cessation, and only low quality evidence for a combination of yoga and cognitive behavioral therapy (25). For alcohol, the results of studies have been mixed, with some reporting a reduction in consumption (26, 27), and others finding no such effects (28) or comorbid psychiatric complaints such as depression (29).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of structured physical activity on behaviors at risk for cardiovascular diseases was also examined in different studies; however, no effects on alcohol use nor smoking habit were observed [ 94 , 95 ] and the effects on sedentary behaviors appeared to be uncertain [ 96 , 97 , 98 ].…”
Section: Physical Activity May Narrow the Mortality Gap Of Depressmentioning
confidence: 99%
“…While concepts and methods continue to evolve, some early results related to smoking cessation and reducing problem drinking among individuals with mental health disorders show promise (8789). However, at this stage, systematic reviews of the evidence on the effectiveness of exercise in promoting abstinence from smoking (60) or alcohol (58) indicate no beneficial effect. On the other hand, the effect of exercise on reducing the use of illegal substances is significant (90).…”
Section: Exercise Is Effective For the Physical Health Of Depressed Pmentioning
confidence: 99%